Tujuh Karakter Fundamentalisme Islam - Tholkhatul Khoir (IAIN Ponorogo, 2014)
Abstract: This article examines fundamentalism and compares it with the concept of extremism, radicalism, and scripturalism. This article discovered that it is possible to carry out study on the phenomenon of fundamentalism in post-positivism paradigm as employed by modern social sciences. As we know that basically all fundamentalism has the same character. However, Islamic fundamentalism are significantly different from the other fundamentalist movements in many substantive things, such as the ability to penetrate the boundaries between countries, the abundance of the activists, the character of the Islam as a